The psychology of music - Deutsch, Dina (San Diego Academic Press, 1982)
The aim of the psychology of music is to understand musical phenomena in terms of mental functions--to characterize the ways in which one perceives, remembers, creates, and performs music. Since the First Edition of The Psychology of Music was published the field has emerged from an interdisciplinary curiosity into a fully ramified subdiscipline of psychology due to several factors. The opportunity to generate, analyze, and transform sounds by computer is no longer limited to a few researchers with access to large multi-user facilities, but rather is available to individual investigators on a widespread basis. Second, dramatic advances in the field of neuroscience have profoundly influenced thinking about the way that music is processed in the brain. Third, collaborations between psychologists and musicians, which were evolving at the time the First Edition was written, are now quite common; to a large extent now speaking a common language and agreeing on basic philosophical issues.The Psychology of Music, Second Edition has been completely revised to bring the reader the most up-to-date information, additional subject matter, and new contributors to incorporate all of these important variables.Show More Show Less